Effect of Cognitive Therapy and Family Psychoeducation in Stroke Clients with Depression and Disability - Arya Ramadia Ramadia; Budi Anna Keliat Keliat; Ice Yulia Wardani Wardani (STIKep PPNI Jawa Barat, 2021)
Stroke patients who were take care in the hospital 30-40% in depression condition. This research aim was to determine the effect of cognitive therapy and psycho Education for depression, helplessness, and ability to change negative thoughts for stroke patients. This research design was quasi experimental pre and post test with control group with a total of sample 87 person with 29 persons are given cognitive therapy and family psychoeducation therapy, 29 persons are given only cognitive therapy and 29 persons are not given therapy. Analysis by anova test and Pair t-test. The result of research show a decrease in depression and helplessness condition and increase the ability to change negative thoughts of stroke clients whom received cognitive therapy and family psychoeducation group larger than whom just only receive cognitive therapy and the group without therapy (p value <0,05). There was factor that contribute depression condition of stroke client is age. Cognitive therapy and Family Psychoeducation are recommended for stroke klien who got depression and helpless to increases the ability to change negative thinking.